2021
DOI: 10.1111/iej.13531
|View full text |Cite
|
Sign up to set email alerts
|

A priori power considerations in Endodontic Research. Do we miss the timeline?

Abstract: Aim To record the prevalence of a priori power calculations in manuscripts published in three endodontic journals between 2018 and 2020 and detect further associations with a number of study characteristics including journal, publication year, study design, geographic region, number of centres and authors, whether the primary outcome pertained to a statistically significant effect and whether confidence intervals (CIs) were reported. Methodology The contents of the three leading endodontic journals with the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In addition, several articles that evaluate retreatment time do not provide sample size calculation or statistical power [3,6,7,19,20]; between 2018 and 2020, 33.9% of articles published in 3 endodontic journals missed a priori sample size calculation and determination of study power, therefore, this is a prevalent problem in the endodontic literature [21]. It is essential to summarize the information on the different techniques for retreatment, as well as the methodologies used to see which are more relevant and can be translated to daily clinical practice [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several articles that evaluate retreatment time do not provide sample size calculation or statistical power [3,6,7,19,20]; between 2018 and 2020, 33.9% of articles published in 3 endodontic journals missed a priori sample size calculation and determination of study power, therefore, this is a prevalent problem in the endodontic literature [21]. It is essential to summarize the information on the different techniques for retreatment, as well as the methodologies used to see which are more relevant and can be translated to daily clinical practice [16].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings, the study of Makou et al (2021) identified study design‐oriented spin , with observational type SRs being mostly affected, whilst again a trend was observed for non‐significant meta‐analyses to be less affected by this flaw (Makou et al, 2021). The former effect has been demonstrated in other types of methodological flaws of original studies as well because observational and non‐randomized studies have been considered of lower quality overall in terms of evidence perspectives (Gratsia et al, 2019; Koletsi et al, 2015; Tzanetakis & Koletsi, 2021b, 2021c). Regarding the latter, one might consider this is related to the overall nature of the identified spin domains, with authors of most SRs being more prone to overstress the conceivably significant findings, disregarding the limitations of the contributing primary studies or overstating a statistically significant p ‐value result (Koletsi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this report, international collaborations as well as trial registration accounted for improved reporting and interpretation, contrary to spin practices. The latter has also been acknowledged universally as a backbone practice for providing transparency and credibility in disseminated research findings (Fleming et al, 2015; Koufatzidou et al, 2019; Tzanetakis & Koletsi, 2021b, 2021c). Similarly, abstracts of RCTs in periodontology and implantology have been reported to present spin in almost 70% of their reports (Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, sample size power calculations were not common in studies assessing root filling material removal. A recent study has shown this to be a prevalent issue in the endodontic literature with an a priori calculation present in only 33.9% of articles between 2018 and 2020 (Tzanetakis & Koletsi, 2021).…”
Section: Experimental Modelsmentioning
confidence: 99%